Synthesis and characterization of microcrystalline and nanocrystalline cellulose from cotton linter for composite applications - Pervin, Sohana; Razzaque, S. M. Abdur Razzaque; Khan, G. M. Arifuzzaman Khan; Shamsul Alam,; Rahman, Moshiur (Vietnam Journal of Science and Technology, 2025)
In this work, microcrystalline cellulose (MCC) and nanocrystalline cellulose (NCC) was synthesized from cotton linter collected from a textile mill in Bangladesh. The synthesis was carried out through several steps; alkali treatment, NaClO2 bleaching and acid hydrolysis. The acid hydrolysis was conducted with 9N and 12N sulphuric acid (H2SO4) for synthesis of MCC and NCC, respectively. The raw and synthesized samples were characterized by measuring bulk density, FTIR, SEM and WAXD techniques. The bulk density of MCC and NCC is higher than that of the raw sample, due to shorter chain length, diameter and reduction of amorphous region of cellulose chain. The oxidation reaction took place during the MCC and NCC preparation was detected by FTIR spectra. From the SEM images, it is seen that the surface of untreated sample looks relatively smooth as compared to the rough surface of treated samples due to voids formation and absence of wax on the surface. The crystallinity index of MCC and NCC was measured from the peaks at 14.6° and 22.6° (2  angles) of WAXD curves. It shows the enrichment in the proportion of crystalline cellulose in MCC. The thermal stability of the MCC is better than that of other experimented samples. Finally, the synthesized MCC and NCC may be emerging and promising materials with exceptional properties.